Integration of flexibility concepts in the management, accounting and financial accounting system: effectiveness of the Agile methodology - G. Cherniyavskyi, Volodymyr (2020)
In a highly competitive, changing environment, organizations face the challenge of ensuring a high level of flexibility and stability. A particularly difficult task is to ensure the flexibility of organizations in the management, accounting and financial accounting subsystem. In this study, the main statement is that the flexibility of management accounting provides flexibility to other subsystems of the organization, forming a generally adaptive structure of the organization to environmental conditions. This article is based on the concept of organizational flexibility and Agile philosophy, which reflects the implications and principles of integration of methodology in accounting systems.